2017
DOI: 10.1089/jmf.2016.0176
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antimicrobial Activities ofCantharellus cibariusFr. (Cantarellaceae)

Abstract: Antibacterial and cytotoxic activities of cyclohexane, dichloromethane, methanol, and aqueous extracts of Cantharellus cibarius were tested. Broth microdilution assay was performed against 10 bacterial strains (Staphylococcus aureus, S. epidermidis, Micrococcus luteus, Bacillus subtilis, Enterococcus feacalis, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella abony), with emphasis on Helicobacter pylori. Methanol extract was the most active against H. pylori strains with minimal inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…Falandysz et al (2017) [ 36 ] also recorded a Cu content of 41 mg/kg d.w. (34–53 mg/kg d.w.) in C. cibarius from Poland, however in these mushrooms from China, it was 31 mg/kg d.w. Smaller amounts of Cu–31.2 mg/kg d.w. were detected by Yildiz et al (2019) [ 28 ] in mushrooms from Turkey, while higher contents were determined by Kolundžić et al (2017) [ 29 ] in C. cibarius from Serbia: 60 mg/kg d.w. Mleczek et al (2016) [ 50 ] observed 18.7 mg/kg d.w. Cu in mushroom species growing near heavily trafficked road in Poland. Cu content in the B. badius ranging from 9.70–13.6 mg/kg d.w. was observed by Mleczek et al (2013) [ 37 ], who were examining fungi from five regions of Poland.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Falandysz et al (2017) [ 36 ] also recorded a Cu content of 41 mg/kg d.w. (34–53 mg/kg d.w.) in C. cibarius from Poland, however in these mushrooms from China, it was 31 mg/kg d.w. Smaller amounts of Cu–31.2 mg/kg d.w. were detected by Yildiz et al (2019) [ 28 ] in mushrooms from Turkey, while higher contents were determined by Kolundžić et al (2017) [ 29 ] in C. cibarius from Serbia: 60 mg/kg d.w. Mleczek et al (2016) [ 50 ] observed 18.7 mg/kg d.w. Cu in mushroom species growing near heavily trafficked road in Poland. Cu content in the B. badius ranging from 9.70–13.6 mg/kg d.w. was observed by Mleczek et al (2013) [ 37 ], who were examining fungi from five regions of Poland.…”
Section: Discussionmentioning
confidence: 95%
“…Comparable manganese contents in C. cibarius were obtained by Ayaz, et al (2011) [ 54 ] 25.2 mg/kg d.w. Brzezicha-Cirocka et al (2016) [ 34 ] determined 30 mg/kg d.w. (20–63 mg/kg d.w.) of this mineral, while Falandysz et al (2017) [ 36 ] detected 38 mg/kg d.w. in C. cibarius from Poland and 19 mg/kg d.w. in this species from China. Yildiz et al (2019) [ 28 ] determined only 4.6 mg/kg of Mn in C. cibarius from Turkey, while Kolundžić et al (2017) [ 29 ] reported up to 41 mg/kg d.w. in this mushroom from Serbia ( Table 5 ). Similar contents of Mn in B. badius from unpolluted areas of the Wielkopolska region, ranging from 11.3 to 14.3 mg/kg d.w. were noted by Mleczek et al (2016) [ 43 ], as well as Karmańska & Wędzisz (2010) [ 42 ] who found 14–17 mg/kg d.w. Kojta & Falandysz (2016) [ 33 ] determined 34.5 mg/kg d.w. in B. badius collected from Kętrzyn and 26.5 mg/kg d.w. in this species from Augustów: Low Mn contents were determined by Mleczek et al (2016) [ 43 ], who were examining B. badius samples from areas where alkaline flotation tailings from Cu production were stored: 1.4–1.8 mg/kg d.w.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All extracts were active against antibiotic resistant H. pylori. Chemical analysis has shown the presence of linoleic, cis-vaccenic, and oleic acids, sterols, β-glucans, and polyphenolic compounds [19].…”
Section: Resultsmentioning
confidence: 99%